Clinical and Immunohistochemical epithelial profile of non-healing chronic traumatic ulcers - Gilligan, Gerardo Marcelo; Panico, René Luis; Di Tada, Cecilia; Piemonte, Eduardo David; Brunotto, Mabel Noemí (2021)
Fil: Gilligan, Gerardo Marcelo. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Medicina Oral; Argentina.